2023
DOI: 10.1039/d2ta09918g
|View full text |Cite
|
Sign up to set email alerts
|

In situconstruction of graphdiyne based heterojunctions by a deprotection-free approach for photocatalytic hydrogen generation

Abstract: Graphdiyne (GDY) with a direct bandgap, high charge carrier mobility, and ordered pore structure, is considered an excellent matrix for the construction of heterojunction photocatalysts. However, the traditional fabrication methods...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…(b) Schematic diagram of GDY/g-C 3 N 4 . Reproduced with permission from ref . Copyright 2023 Royal Society of Chemistry.…”
Section: Gdy-based Carbon Nitride Photocatalystmentioning
confidence: 99%
“…(b) Schematic diagram of GDY/g-C 3 N 4 . Reproduced with permission from ref . Copyright 2023 Royal Society of Chemistry.…”
Section: Gdy-based Carbon Nitride Photocatalystmentioning
confidence: 99%
“…Wang et al reported the GDY@C 3 N 4 synthesized by a deprotection-free approach. The photocatalytic hydrogen yield of GDY@C 3 N 4 was 15.6-fold of that of pristine C 3 N 4 . Mao and co-workers reported an Ag 3 PO 4 /GDY-based Pickering emulsion for water photooxidation and photodegradation of methylene blue .…”
Section: Graphdiyne-based Catalytic Materialsmentioning
confidence: 99%
“…The photocatalytic hydrogen yield of GDY@C 3 N 4 was 15.6-fold of that of pristine C 3 N 4 . 138 Mao and co-workers reported an Ag 3 PO 4 /GDY-based Pickering emulsion for water photooxidation and photodegradation of methylene blue. 139 As an electron acceptor, graphdiyne transported photogenerated electrons from Ag 3 PO 4 , promoting water oxidation on the Ag 3 PO 4 active sites.…”
Section: Graphdiyne-based Catalytic Materialsmentioning
confidence: 99%
“…In addition to these examples, other functional GDY nanoarchitectures, such as CuCo 2 O 4 /GDY heterostructure, [158] C 3 N 4 /GDY heterostructure, [84,148] Co 3 O 4 QD/GDY heterostructure, [61] CoS 2 NW/GDY heterostructure, [81] double Sscheme ZIF-67@GDY/CuI heterostructure, [159] S-scheme ZnCdS/GDY heterostructure, [160] GDY/CuMoO 4 /CuO heterostructure, [161] and GDY/CuI/NiO, [162] have been rationally designed to optimize the reaction overpotential, electron density, and carrier transfer capability for impressive H 2 production activity.…”
Section: Hermentioning
confidence: 99%